Comparison of CVF (Cyclophosphamide+Vinorelbine+5-Fluorouracil) and CMF (Cyclophosphamide+Methotrexate+5-Fluorouracil) Adjuvant Chemotherapy in Early Breast Cancer - Gwak, Geumhee (Korean Breast Cancer Society, 2011)
PURPOSE: Our study aimed to evaluate the feasibility of adjuvant cyclophosphamide/vinorelbine/5-fluorourail (CVF) chemotherapy as an alternative to cyclophosphamide/methotrexate/5-fluorouracil (CMF) chemotherapy for treating early breast cancer. METHODS: One hundred and forty-nine patients were randomly assigned to CMF or CVF adjuvant chemotherapy for treating their early stage breast cancer between September 2000 and December 2007. The disease-free survival (DFS), the overall survival (OS), and the toxicity profiles of both groups were compared. RESULTS: Sixty-seven patients underwent CMF chemotherapy whereas 82 patients underwent CVF chemotherapy. The DFS and OS were 88 months (95% confidence interval [CI], 76-101 months) and 94 months (95% CI, 83-104 months), respectively for the CMF group, and 97 months (95% CI, 93-101 months), and 101 months (95% CI, 98-104 months), respectively for the CVF group. However, those survival gains of the CVF group were not statistically significant (p-value=0.069 for the DFS and 0.99 for the OS). The CVF group showed a favorable toxicity profile in terms of the grade 3/4 hematologic toxicities as compared to that of the CMF group. CONCLUSION: Clinical outcome of CVF chemotherapy was comparable to CMF with a favorable toxicity profiles. However, it is difficult to conclude the feasibility of CVF regimen because of small number of studied patients.